Software Maintenance Success Recipes - Reifer, Donald J (Auerbach Publications, 2011)
Software Maintenance Success Recipes identifies actionable formulas for success based on in-depth analysis of more than 200 real-world maintenance projects. It details the set of factors that are usually present when effective software maintenance teams do their work and instructs on the methods required to achieve success.